Unbiased constrained adaptive IIR notch filter using direct frequency estimation algorithm - Punchalard, R.; Lorsawatsiri, A.; Loetwassana, W.; Koseeyaporn, J.; Wardkein, P.; Roeksabutr, A. (My University, 2007)
An unbiased constrained direct adaptive IIR notch filter is presented in this paper. The proposed algorithm employs the bias removal technique to remove the bias existing in the estimate of the filter parameter, resulting in good estimate of filter parameter. The theoretical analysis for the difference equation for the convergence in the mean is derived in closed form and confirmed by the computer simulations. ©2007 IEEE.